Implementasi Sistem Aplikasi Penjualan Sayur Dan Buah (Studi Kasus : Ud Mr Putra) - Mardiansyah, Muhammad Rizki; Fauzi, Amir Hasanudin (eProceedings of Applied Science, 2024)
Mobile-based applications are starting to develop in Indonesia. With the development of mobile applications, some of the life problems experienced by society starting to resolve. Currently UD MR PUTRA wants to enter the era digital which utilizes mobile application technology to make his business easier. Through this application it is hoped the transaction process for buying and selling vegetables and fruit becomes more efficient and transparent, and UD MR PUTRA owners can get more easy to manage stock and product information. Besides that, This application is also expected to simplify the process purchasing vegetables and fruit for UD MR PUTRA partners. With This step, UD MR PUTRA aims to improve market competitiveness and offer a better experience for its customers in today's digital era. Keywords— Mobile Application, Vegetable and Fruit Sales, Inventory Management